KDM6A Deficiency Induces Myeloid Bias and Promotes CMML‐Like Disease Through JAK/STAT3 Activation by Repressing SOCS3 - Huiqiao Chen; Shufen Wang; Ruoyu Dong; Pinhui Yu; Tianyu Li; Liangning Hu; Mowang Wang; Zijun Qian; Hongyu Zhou; Xiaoyan Yue; Limengmeng Wang; Haowen Xiao (Advanced Science)
Abstract Chronic myelomonocytic leukemia (CMML) is a hematologic malignancy with a poor prognosis and limited targeted therapies. Lysine demethylase 6A (KDM6A), a H3K27 demethylase and key component of the COMPASS complex, is frequently mutated in hematologic malignancies, but its roles in embryonic hematopoiesis and tumor suppression in CMML remain unclear. Using zebrafish models with kdm6a mutants and integrative multi‐omics analysis (ATAC‐seq, RNA‐seq, ChIP), we find that Kdm6a is a critical positive regulator of hematopoietic stem and progenitor cell (HSPC) emergence via Syk‐related inflammatory signaling in a H3K27me3‐dependent manner. We further find that Kdm6a haploinsufficiency in zebrafish leads to myeloid‐biased hematopoiesis and a CMML‐like disease, similar to CMML patients with reduced KDM6A expression. This KDM6A haploinsufficiency also significantly alters the chromatin landscape of genes associated with aging and cellular homeostasis in HSPCs. Mechanistically, KAM6A haploinsufficiency represses SOCS3 expression, thereby activating JAK/STAT3 signaling in HSPCs. Importantly, inhibitors targeting JAK or STAT3 phosphorylation alleviate myeloid expansion, providing a rationale for JAK/STAT pathway inhibition in CMML therapy. These findings enhance our understanding of CMML pathogenesis and propose new therapeutic avenues.